Vattenbehov och olika system för vattentilldelning till nyavvanda grisar - Lindgren, Hanna (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
We all know that water is very important for both animals and humans. When we are weaning the piglets from the sow we must guarantee that the piglets can start to drink more water instead of sow milk. The first thing to check is always the quality of the water that is to be used. To secure that, you must take a water sample. If the water is inadequate it can bring a lot of problems and diseases. It's also important to choose the right water system for the piglets, so that the water requirements is fulfilled. The faster the newly weaned pigs start to drink the faster will they begin to grow. The aim of the study, that was made in connection to this work, was to register differences between newly weaned pigs in two types of water systems. Two pens with ten pigs each were used. In one pen the piglets had a water nipple and in the other pen they had a water cup with a water mirror. Both pens were video taped and it was documented how many times the piglets visited the water place. Feed consumption and individual weight gain of the pigs were also registered in the two pens. The results for drinking behavior showed more drinking visits per pig in the pen with water mirror compared to the pigs who had water nipple. The number of noses spilled water was actually higher for the pigs with water nipple. You can see that the two groups of piglets had the same feed consumption but the piglets with water mirror gained more weight than the piglets in the other box. It was also less activity in the pen with water mirror.